Molecular screening of the human parvoviruses B19 and bocavirus 1 in the study of congenital diseases as applied to symptomatic pregnant women and children. Issue 5 (20th June 2019) - Salbetti, Maria Belen; Pedranti, Mauro Sebastian; Barbero, Paula; Molisani, Paula; Lazzari, Martina; Olivera, Nicolas; Isa, Maria Beatriz; Bertoldi, Ariel; Moreno, Laura; Adamo, Maria Pilar
Abstract : Introduction. B19 virus (B19V) and bocavirus 1 (HBoV1) are human pathogenic parvoviruses that are prevalent worldwide and are responsible for a diverse and not yet fully established spectrum of clinical manifestations. Objective. To screen B19V and HBoV1 in patients with clinical manifestations associated with acquisition of the infection during gestation. Methods. A retrospective, observational study was performed that included serum samples from patients without a previous known aetiology. B19V and HBoV1 were determined by end-point PCR. Positive samples were genotyped. Results. A total of 106 serum samples were analysed, 61 from pregnant women and 45 from neonates and paediatric patients. None were positive for HBoV1, while B19V was detected in 37/106 [34.9 %, 95 % confidence interval (CI): 26.5–44.4] of the samples studied. In the group of pregnant women, 28/61 (45.9 %, 95 % CI: 34.0–58.3) were B19V-positive, and 2 of them had foetal anaemia followed by hydrops and foetal death, 3 were associated with a history of recurrent pregnancy loss and there was 1 case of spontaneous abortion. B19V was also detected in cases of maternal febrile exanthema, polyhydramnios, oligohydramnios and foetal ascites. In the group of children, 9/45 (20.0 %, 95 % CI: 10.9–33.8) neonatal patients were B19V-positive, and this was associated with foetal hydrops, TORCH syndrome and cardiac alterations. The nucleotide sequences analysed confirmed the identity of B19V genotype 1. Conclusions. We found no evidence to indicate the presence of HBoV1 in maternal blood or in the newborns/paediatric patients (hence providing no support for the supposed vertical transmission). On the other hand, the high frequency of B19V in the pathologies studied indicates the importance of molecular diagnosis in both the mother and the child. Future efforts should contribute to early detection and characterization of infections.